Women and post-conflict reconstruction: Issues and sources - Birgitte Sørensen (United Nations Research Institute for Social Development (UNRISD), 1998)
Women and Post-Conflict Reconstruction: Issues and Sources is a review of literature dealing with political, economic and social reconstruction from a gender perspective. One of its objectives is to go beyond conventional images of women as victims of war, and to document the many different ways in which women make a contribution to the rebuilding of countries emerging from armed conflicts. Special attention is given to women's priority concerns, to their resources and capacities, and to structural and situational factors that may reduce their participation in reconstruction processes. A second aim is to shed light on how post-war reconstruction processes influence the reconfiguration of gender roles and positions in the wake of war, and how women's actions shape the construction of post-war social structures. Following the brief Introduction is a chapter on political reconstruction. It raises questions concerning women's participation in peace-building and democratization. In order to illuminate women's expectations regarding their roles and status in post-war society, the chapter opens with a brief discussion of how and to what extent various liberation movements have addressed women's issues. While some movements considered women's issues to detract attention from the main goal of their struggle, many movements regarded women's liberation as an integral dimension of their overall struggle for social justice. The fact that women's issues were included on the political agendas and that women themselves were mobilized to participate actively in the fighting is demonstrated to have been instrumental in raising women's political awareness and their expectations of state and society today. The ensuing discussion of women's participation in formal and informal peace-building activities shows that in most cases women are excluded from formal peace negotiations. Such high-level negotiations are identified as male domains, which means that they also employ discourses and practices that are closer to men's reality than to women's. As a result, women also lack direct influence in the identification of reconstruction priorities that are usually part of a peace agreement. Nevertheless, women are demonstrated to play an influential role through their work in grassroots organizations working for peace and reconciliation. From within these organizations, women constantly challenge the authorities and other members of society with demands for peace, non-discrimination, accountability, recognition of human rights, etc. While always positioned on the margins, these organizations show their ability to mobilize large numbers of women, and to translate individual grievances into legitimate social concerns. Moreover, many of them play a significant role in building a new culture of peace at the local level by organizing peace education and community-based reconciliation and social reconstruction activities. Democratization processes are generally applauded, because they are assumed to guarantee accountability and to grant all citizens the possibility to participate in political life. However, studies on elections and decentralization demonstrate several flaws when it comes to women's position. Many countries emerging from armed conflict have adopted new constitutions that grant women equal political, social and economic rights, and many governments have developed new quota systems to ensure women equal representation in decision-making institutions at all levels. However, the implementation of these laws and good intentions often runs into major obstacles. At the government level the problems include a lack of financial resources and a lack of gender awareness or political will among staff. Other major problems are to be found at the social level, where the new discourse of gender equality may run counter to existing social norms regarding gender roles. The examples discussed show that, in some cases, local authorities and male members of society may discourage or prohibit women from participating in political activities. Moreover, the fact that the division of labour has not changed in favour of women, but rather added to their burden, also poses practical limitations on the possibilities for active involvement of women. Despite these constraints, women have made remarkable contributions in many countries. In the context of elections women have organized civic education targeting women, and they have convinced women of the importance of their vote. Educated women have organized legal counselling to inform women about their rights and to help them exercise these rights. Chapter three deals with economic reconstruction and the strategies that women develop to cope with war-induced changes in the economic environment and to meet the growing responsibilities for the survival and well-being of family and relatives. The focus is on the relationship between women's economic activities and their socio-economic position. The first section of the chapter concentrates on women's involvement in agricultural production, which often constitutes a major source of income. In addition to problems of landmines, a lack of agricultural inputs and farm implements, a shattered infrastructure and the inaccessibility of markets, etc., which equally trouble male farmers, women face a number of particular challenges. First, women often lack legal rights to land and other resources which, in the context of social disintegration where a large number of women become single providers, may reduce their ability to survive on farming alone. In some countries, women are organizing themselves to lobby state and local authorities for increased access to such resources, but in many cases women are forced off the land and are compelled to seek other sources of income. Another problem facing women in agriculture is the dismantling of traditional work groups due to displacement, divorce, death, etc. This has often resulted in the creation of new co-operative associations and voluntary self-help groups which combine old institutions and current social conditions. When cultivating the family land is no longer an option, some women join the casual agricultural labour force. While this opportunity enables women to employ their skills and to earn an income, recent analyses suggest that this may in fact mean that women come to occupy a marginal position in the new structure of rural social stratification. Another area which proved to be of great importance to women's livelihoods was the burgeoning informal sector, with petty trade and small-scale businesses as major sources of income. The documentation of women's involvement in this sector showed a great variety in experiences. Some women took up activities in which they had also been involved prior to the war, but many engaged in innovative projects, even when it meant a break with existing social norms, as they took up jobs perceived to be male jobs. Some women established businesses on the basis of local resources and demand, while others established elaborate trading networks which cut across ethnic boundaries and national borders. Again, women's capacity to build and mobilize extensive social networks had a positive impact. But while women generally proved to be eager and capable entrepreneurs, the sustainability of their enterprises was often constrained by a lack of capital and marketing skills, not to mention the fact that the sector itself is highly insecure and fluctuating. Moreover, women's economic success would in some cases result in social stigmatization and exclusion, due to clashes with prevailing norms or jealousy. Finally, the formal sector is discussed. For various reasons, societies emerging from war usually experience a high unemployment rate, and women are often particularly marginalized with regard to access to formal employment. In some cases this is a result of the fact that women generally have poorer educational qualifications, but research also suggests that discriminatory practices are still frequent. One of the few areas where women seem privileged is the social sector, but because this sector is often exposed to budgetary cuts, women's access to income and status from this field is reduced. Nevertheless, women continue to perform related tasks, but as semi-professionals or even as volunteers. The fourth chapter focuses on social reconstruction, specifically on the rehabilitation of social services (health care and education) and wider issues of social integration. With regard to the first aspect, the main questions are whether the social sector recognizes women's particular needs, and whether it seeks to build on women's skills and capacities. The discussion on social integration shifts the focus to how women are positioned in processes of inclusion and exclusion, and to how women's strategies and activities influence social integration. Studies on the rehabilitation of social services suggest that even though women's needs and rights are increasingly recognized officially, women continue to be discriminated against with regard to access to education for social and cultural reasons. Health care and other social facilities also remain inadequate, with consequences not only for women's health, but also for their ability to participate in political and economic life. The material clearly demonstrates that social issues were generally given high priority by women themselves, and many women in post-conflict societies make a major contribution to their rehabilitation. In rural as well as urban areas, women have re-established primary education for children as a means to build local capacities and influence their socialization, and women are often involved in providing primary health care and socio-economic assistance on a self-help basis to people in crisis. However, as noted above, while such activities are generally welcomed, they are often considered but a natural extension of women's domestic obligations and hence are not remunerated or responded to with offers of training. In addition to ordinary health care problems, intrastate wars produce a number of specific health problems known as psycho-social traumas. These traumas may stem from experiences of forced displacement, torture, rape, violence, witnessing killings, etc. In some cases, women have been particularly vulnerable to this kind of assault on mind and body. But women have also been very active in addressing the scars that such experiences leave, organizing voluntary organizations which offer medical and psychological treatment. Moreover, they have helped former victims to overcome their distress and reintegrate, by offering skills training and income-generating activities. Another issue which has been addressed by women's organizations is the growth of violence within post-war societies. Through classroom education and workshops, women have sought to raise awareness about violence against women and to change the attitudes that consider such violence acceptable. As the discussion on social integration points out, there has long been a tendency to focus exclusively on the reintegration of returnees, internally displaced persons and demobilized soldiers, or of persons who have become marked and marginalized due to torture, disability, widowhood, etc. However, to the extent that any post-war society is inevitably undergoing profound changes in its socio-economic and political composition, the issue of integration is relevant to all members of society. This chapter focuses on this aspect from a gender and family perspective, and shows how integration often also has disintegrative aspects. Newly gained economic freedom and independence, long years of separation and exposure to new social environments and attitudes, new perceptions of the role of the family and its members, and forced migration in search of employment, all contribute to continued dismantling of existing social institutions and the establishment of new ones. Social integration, in other words, is not simply about "coming home", but about defining new guiding social values and establishing corresponding relationships and institutions based on a combination of factors including kinship, socio-economic interests, and shared experiences and circumstances. In the final chapter, conventional conceptualizations of women in conflict and post-conflict situations are examined. The chapter also contains some suggestions for alternative concepts and approaches which appear to be better tools for our understanding of women's situation and thus for the development of programmes that will assist women in their multiple efforts to rebuild their lives. It is pointed out that our understanding of women's roles in post-war societies and of their contributions to post-war reconstruction must go beyond the universalistic narrative of "women's experience of war". The specificity and diversity of women's experiences must be acknowledged. Only on this basis can we conduct comparative analyses and begin to develop a deeper general understanding of post-war reconstruction from a gender perspective. Second, the concluding chapter stresses the need to supplement the image of women as vulnerable victims with an image of women as a highly differentiated group of social actors, who possess valuable resources and capacities and who have their own agendas. Women influence the course of things, and their actions are constitutive of post-war societies. The reduction of women to targets and beneficiaries both fails to recognize their contributions and contributes to their marginalization. A third point stressed in the conclusion is the need for gender-specific data and gender-focused analysis. While special attention is given to women throughout the publication, so as to make visible the previously invisible, the aim has been to see women's situation within a gender framework which pays attention to how gender roles and relationships are continuously constructed and contested by different actors, and which recognizes the gender dimension inherent in all aspects of post-war reconstruction. The gender perspective is also relevant for the achievement of sustainable peace. As the analysis strongly suggests, the failure to recognize gender issues may produce new social tensions and contribute to the differentiating struggles over identity, status and power that are so distinctive for societies which have recently achieved peace.
Keywords: 330